Design and Implementation a Wearable Vital Signs Monitoring System with Low Power Consumption and Measurement Validation - Ajaj , Rshwan Aodah Mosbah; Kadhem , Haider Majid Hamid; Nori , Aqeel Hameed; Issa , Mujtaba Mansour (American Journal of Botany and Bioengineering, 2025)
The importance of applying E-Health systems is considered as a standard for the advancement and well-being of people. Wearable devices classified as part of mobile health systems, which is considered as one of E-Health, used to monitor patients.They are widely used to monitor vital signs of patients outside the health institution’s environment, compensating for the monitoring devices from the hospital. The most important challenges facing wearable health systems are the accuracy of measurement, power consumption, and compact size. The purpose of this reserch is to design a device that can be worn at a low cost and of a small size to provide comfort to the patient. . The results showed that the device is 99.37% accurate and statistical analysis was performed to test the error. Also, the results showed that the error of the device is small and that outlier values are rarely frequent, which means that the error does not affect the accuracy of the system.